PRODUKSI ENZIM LIPASE DARI Aspergillus niger ISOLAT KAPANG KOPRA DENGAN MENGGUNAKAN MEDIUM KELAPA PARUT - Indah Indah; Mappiratu Mappiratu; Musafira Musafira (KOVALEN: Jurnal Riset Kimia, 2017)
The investigation about the lipase enzyme production from Aspergillus niger using grated coconut as a medium has been done. The aim of the study is to determine the best incubation time, pH and water content which produced lipase enzyme with high activity. Randomized Block Design (RBD) with 2 factorial pattern (incubation time and pH of the medium) was used in this research. Each factor consists of three levels and it was done in the triple. The level of incubation time and of pH were 48, 60, 72 hours and pH 5, 6, and 7, respectively. The observed parameter was the obtained lipase enzyme activity. The result showed that the highest activity was achieved at pH 7 for 48 hours of incubation time with 45% of water content. The amount of lipase enzyme activity was 1.70 µmol/ml.minutes.Keywords: mold coconut, Aspergillus niger, lipase